3D printing with MRI in pediatric applications. Issue 6 (22nd July 2019) - Parthasarathy, Jayanthi; Krishnamurthy, Ramkumar; Ostendorf, Adam; Shinoka, Toshiharu; Krishnamurthy, Rajesh
Abstract : 3D printing (3DP) applications for clinical evaluation, preoperative planning, patient and trainee education, and simulation has increased in the past decade. Most of the applications are found in cardiovascular, head and neck, orthopedic, neurological, urological, and oncological surgical cases. This review has three parts. The first part discusses the technical pathway to realizing a physical model, 3DP considerations in pediatric MRI image acquisition, data and resolution requirements, and related structural segmentation and postprocessing steps needed to generalize both virtual and physical models. Standard practices and processing software used in these processes will be assessed. The second part discusses complementary examples in pediatric applications, including cases from cardiology, neuroradiology, neurology, and neurosurgery, head and neck, orthopedics, pelvic and urological applications, oncological applications, and fetal imaging. The third part explores other 3D printing applications and considerations such as using 3DP to develop tissue‐specific phantoms and devices for testing in the MR environment, to educate patients and their families, to train clinicians and students, and facility requirements for building a 3DP program. Level of Evidence: 5 Technical Efficacy: Stage 5 J. Magn. Reson. Imaging 2020;51:1641–1658.